Pengaruh Hubungan Manusiawi, Stres Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Produksi Pada PT. Cimory - Putri, Vera Eselia; Sunaryo, Hadi; Amin, Muhammad Sirojuddin (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to analyze the influence of human relations, work stress and work motivation on the performance of production employees at PT. Cimory. This type of research focuses on explanatory research with a quantitative approach. The population in this study were production employees of PT. Cimory, Pasuruan Regency. A sample of 68 employees was determined using the Slovin formula. Data analysis was carried out using SPSS, including validity test, reliability test, normality test, classical assumption test, hypothesis test and coefficient of determination test (R2). The results of the research show that human relations and work motivation have a significant effect on the performance of PT production employees. Cimory. Meanwhile, work stress does not have a significant influence on the performance of PT production employees. Cimory. Keywords: Human Relations, Work Stress, Work Motivation, Production Employee Performance.